Sensitive Indicators to Rehabilitation Nursing Care in a Rehabilitation Program for People in the Surgical Process, Based on the Health Quality Model. - Nascimento, VANIA (2019)
Abstract Continued improvement in care is one of the primary objectives of Rehabilitation Nursing. With the current medical-surgical evolution, the Rehabilitation Nurse faces new challenges related to the recovery, enhancement and maintenance of the functionality and capacity of the person in the surgical process. The identification of the indicators that are sensitive to the care of Rehabilitation Nursing, presents in the intervention plans carried out, allow us to measure the quality of the care provided and guarantee the excellence of the care performed. Objective: To identify sensible indicators for Rehabilitation Nursing care, presents in the Rehabilitation programs executed to the person in the surgical process, based on the health quality model. Methods: A systematic review of the literature was carried out through the EBSCO host (MEDLINE with Full Text, CINAHL Plus with Full Text and MedicLatina), using the PI [C] O method. Results: 49 indicators were identified, with emphasis on: “Percentage of clients to whom rehabilitation plan and/or rehabilitation program has been implemented to maximize functional capabilities”; “Percentage of clients with potential to improve the walking ability” and “Percentage of clients with risk of muscle stiffness who were monitored for the range of joint motion through the goniometer”. Conclusion: The surgical patient, in the various areas of intervention (vascular, neurosurgical, orthopedic), presents health gains with the implementation of Rehabilitation programs, with 49 indicators that are sensitive to Rehabilitation Nursing care in the programs executed.